Model Pembelajaran Inkuiri Sebagai Strategi Mengembangkan Kemampuan Berpikir Kritis Siswa - Mochammad Bagas Prasetiyo; Brillian Rosy (Universitas Negeri Surabaya, 2020)
This article discusses how inquiry learning models as a strategy develop students' critical thinking skills. The basic competency used for this learning purpose are management functions. In the learning process in the classroom teachers are expected to be more varied in providing learning models, because the problem that often occurs at this time is the delivery of material that is not right makes students feel bored and bored resulting in not focusing on learning. The role of the teacher here is very important when determining the methods and models of learning to be delivered must be adjusted to the basic competencies of the subject matter. The Inquiry Learning Model is felt to be able to change the mindset of students who initially only focused on the teacher and passive in the classroom, became more critical in solving problems encountered and can find answers to the questions they asked. Inquiry learning is very important for students not only in schools, but in the environment in which they are located, because inquiry relies on the ability of each individual to solve existing problems and bring up their critical thinking skills and innovation and creativity. This type of research is conceptual which proves inquiry learning model that can improve students' critical thinking skillson learning management functions.